An experimental assessment of reproductive isolation and its consequences for seasonal hybridization dynamics. (4th December 2018) - Foucault, Quentin; Wieser, Andreas; Heumann-Kiesler, Clara; Diogo, Joao; Cocchiararo, Berardino; Nowak, Carsten; Waldvogel, Ann-Marie; Pfenninger, Markus
Abstract: While the spatial aspect of hybridization has been investigated in depth, the temporal aspect has not. We analysed the seasonal hybridization dynamics of a multivoltine non-biting midge sister species pair, Chironomus riparius and C. piger . We investigated the fertility and fitness of F1 hybrids, and all possible first-generation backcross hybrids, under different temperature conditions. Based on microsatellite markers, we then inferred the presence of different hybrid classes in seasonal field samples (spring and autumn) from a site of co-occurrence over two consecutive years. All experimental hybrids showed reduced fertility albeit without a specific temperature effect. Fitness was zero in one F1 direction, but not reduced in the other. No sex ratio distortion was observed. However, fitness was reduced in all backcrosses, indicating that hybridization should be rare in the field. In the seasonal samples, C. piger was found only in autumn individuals. All 359 genotyped individuals were attributed to either of the pure species. However, several individuals of the autumn samples carried signs of later generation introgression, indicating that actual hybridization must take place recurrently during summer. We thus present evidence that seasonal environmental changes can drive hybridization dynamics and that long-term recurrent hybridization need not affect species integrity.